The Influence of Sharia Accounting Implementation on the Financial Performance of Islamic Banks in Qatar - Ai Netty Sumidartiny; Muhammad Fazlurrahman Syarif; Murniati Mukhlisin (Perbanas Journal of Islamic Economics and Business, 2026)
Purpose: This study aims to analyze the influence of the implementation of Islamic accounting based on AAOIFI standards on the financial performance of Islamic banks in Qatar. Methodology: Financial performance is measured using three key indicators: Return on Assets (ROA), Return on Equity (ROE), and Net Profit Margin (NPM). The research data were collected from six leading Islamic banks in Qatar during the period of 2019 to 2023, employing a quantitative method and linear regression analysis to test the relationship between the level of compliance with Islamic accounting standards and financial performance. The AAOIFI compliance measurement instrument was developed through a Likert-scale questionnaire that was tested for validity and reliability. Findings: The results indicate that the implementation of Sharia accounting has a positive and significant effect on all three financial performance indicators. Specifically, every one-point increase in the AAOIFI compliance score raises ROA by 0.02%, ROE by 0.105%, and NPM by 0.215%. The regression model explains 38% to 47% of the variance in financial performance, suggesting that applying Sharia accounting standards plays a critical role in improving asset management, equity efficiency, and net profit generation in Islamic banks. Orginility: These findings reinforce the importance of integrating AAOIFI standards into Islamic banks’ financial reporting to enhance transparency, accountability, and competitiveness. This study provides practical implications for Islamic bank management and Islamic financial regulators, particularly in promoting the global harmonization of Sharia accounting standards. Furthermore, this research serves as a reference for future studies to examine Sharia governance aspects and other moderating variables.